Legal Aspects of Transparency in the Eurasian Economic Union - BOKLAN, Daria; LIFSHITS, Ilya (Journal of Advanced Research in Law and Economics, 2018)
The transparency principle has a particularly vital role in international economic integration organizations because states delegate their sovereign powers to such organizations. Legal instruments applicable within such organizations display an evident deficiency of democratic legitimacy, as they have extensive power to affect human rights, while in contrast, many bodies representing the people are granted only limited participation in decision-making processes or are not involved in them at all. These characteristics place particular importance on the transparency principle, and the implementation of this standard is in the majority of cases a pre-condition of civil society’s effective control over international economic organizations, their accountability, and ultimately good governance. The Eurasian Economic Union (EAEU) is a newly created regional and international organization, which aims at fostering economic cooperation between post-soviet states, managing a customs union and creating a single economic space in the territory of its members. Several questions arise in relation to EAEU activities: Is the EAEU a purely intergovernmental organization focused solely on trade issues, or could it be a real union that can support the ideas of accountability, good governance and the rule of law? What is the role of the transparency principle in building such an institution? This article tries to answer these questions.